Cuararizantes use in care delivery - Squire, J. (2015)
The author's experience with the use of "curare" in pregnant women in labor in the course of 30 years is presented. The author indicates that the advantage of using curare during induction of anesthesia is that you can easily manage a poor light anesthesia inhalation in a well-sedated patient, being able to make any obstetric surgical procedure, including the implementation of mid-forceps, under conditions optimal.